Reaction Channel selection techniques and γ – γ fast-timing spectroscopy using the ν-Ball Spectrometer. (December 2020) - Canavan, R.L.; Rudigier, M.; Regan, P.H.; Lebois, M.; Wilson, J.N.; Jovancevic, N.; Söderström, P.-A.; Thisse, D.; Benito, J.; Bottoni, S.; Brunet, M.; Cieplicka-Oryńczak, N.; et al.
Abstract: The reaction of a pulsed 18 O beam on a self-supporting and gold-backed isotopically-enriched 164 Dy target of thickness 6.3 mg/cm 2 at separate primary beam energies of 71, 76 and 80 MeV was studied at the accelerator at the ALTO facility of the IPN Orsay. The γ rays produced were detected using the newly-constructed ν-Ball spectrometer which comprised of HPGe and LaBr3 (Ce) detectors. This conference paper describes the methodology and effectiveness of multiplicity/sum-energy gating, for channel selection between fusion evaporation events and lower multiplicity/energy events from inelastic nuclear scattering and Coulomb excitation of the target, and from two-neutron transfer reactions to 166 Dy.